Construction Techniques for Strengthening of Dongming Yellow River Road Bridge by the Cable-Stayed System. (November 2019) - Xu, Gangnian; Wang, Laiyong; Wu, Junyan; Zhang, Jianjuan
Abstract: The Dongming Yellow River Highway Bridge (75+7×120+75 m), is a large span prestressed concrete rigid frame and continuous combination beam bridge, which was the first bridge strengthened by cable-stayed system in China. Using towers and stay cable system, the main bridge was transformed to provide vertical support with superstructure. For the foundation reconstruction, bored piles were constructed as new pile foundations on both sides of the original pile foundations. After cofferdam pumping, to ensure the positioning of the protective tubes, the reinforcing bars, concrete cover and concrete piles left in the river bed were removed by using brush drilling rigs, long arm digging machines and frogmen, while the "U-tube" method was used to grout at the bottom of the piles. The diamond wire saw cutting technology was adopted to complete the transformation of the old caps and insert shear nails. Using the post-pouring strip temporary shields, the new caps and old caps were connected until the tensioning of the cables was finished. To ascertain the arrangement of the reinforcement on the floor and the prestressed reinforcement, and then stick the positioning plates on the floors, bonded rebars holes were drilled utilizing the hydraulic core drill that was made. The joists and the brackets are manufactured by the factory and assembled in the construction site. Gantry cranes and angle fine-tuning devices were used to install the joists and brackets, and then the connecting bolts were inserted. Concurrently, material was transported through the hole in the roof of the middle-span, and the steel supports within the box were installed. From the middle towers to the side towers, from the short cables to the long cables, cables were tensioned by batches and levels with constant monitoring throughout the whole process of this tensioning construction. Finally, the external prestressed strands inside the box were adjusted and the bridge deck construction was completed.